A New P‐Wave Tomographic Model (CAP22) for North America: Implications for the Subduction and Cratonic Metasomatic Modification History of Western Canada and Alaska. Issue 3 (9th March 2023) - Boyce, A.; Liddell, M. V.; Pugh, S.; Brown, J.; McMurchie, E.; Parsons, A.; Estève, C.; Burdick, S.; Darbyshire, F. A.; Cottaar, S.; Bastow, I. D.; Schaeffer, A. J.; et al.
Abstract: Our understanding of the present‐day state and evolution of the Canadian and Alaskan mantle is hindered by a lack of absolute P‐wavespeed constraints that provide complementary sensitivity to composition in conjunction with existing S‐wavespeed models. Consequently, cratonic modification, orogenic history of western North America and complexities within the Alaskan Proto‐Pacific subduction system remain enigmatic. One challenge concerns the difficulties in extracting absolute arrival‐time measurements from often‐noisy data recorded by temporary seismograph networks required to fill gaps in continental and global databases. Using the Absolute Arrival‐time Recovery Method (AARM), we extract >180, 000 new absolute arrival‐time residuals from seismograph stations across Canada and Alaska and combine these data with USArray and global arrival‐time data from the contiguous US and Alaska. We develop a new absolute P‐wavespeed tomographic model, CAP22, spanning North America that significantly improves resolution in Canada and Alaska over previous models. Slow wavespeeds below the Canadian Cordillera sharply abut fast wavespeeds of the continental interior at the Rocky Mountain Trench in southwest Canada. Slow wavespeeds below the Mackenzie Mountains continue farther inland in northwest Canada, indicating Proterozoic‐Archean metasomatism of the Slave craton. Inherited tectonic lineaments colocated with this north‐south wavespeed boundary suggest that both the crust and mantle may control Cordilleran orogenic processes. In Alaska, fast upper mantle wavespeeds below the Wrangell Volcanic Field favor a conventional subduction related mechanism for volcanism. Finally, seismic evidence for the subducted Kula and Yukon slabs indicate tectonic reconstructions of western North America may require revision. Plain Language Summary: Our understanding of the plate tectonic history of North America is incomplete. Outstanding questions include: 1. Have ancient parts of the North American plate been modified over time or remained unchanged since assembly? 2. What processes produced the differing shape of the western Canadian Cordilleran Mountains along their length? 3. Can we image the old plate remnants that were recycled back into the mantle at subduction zones to better understand how North America was formed? We use earthquakes that produce P‐waves, recorded at distant receivers, to seismically image the mantle below North America, including new data from Canada and Alaska for the first time. Slower‐than‐expected seismic wavespeeds that continue from the west coast inland toward north‐central Canada suggest the ancient Slave Craton has been modified by chemical processes ≥500 million years ago. An abrupt seismic wavespeed boundary perpendicular to the Canadian Cordilleran Mountains suggests their shape may be controlled by pre‐existing zones of weakness in the crust and mantle. Fragments of old tectonic plates, stuck in the mantle below western North America and Alaska, suggest our understanding of the final stages of assembly of modern North America requires revision. Key Points: North American absolute P‐wavespeed tomographic model incorporating dense seismic networks in Canada and Alaska Imaged fast wavespeed subducted remnants suggest revision of Alaskan and proto Pacific subduction models is necessary Slow wavespeed structures imply Slave Craton metasomatic modification and tectonic inheritance during Cordilleran orogenesis